2015
DOI: 10.1093/ntr/ntv111
|View full text |Cite
|
Sign up to set email alerts
|

The Social Patterning of Tobacco Use Among Women in Jordan: The Protective Effect of Education on Cigarette Smoking and the Deleterious Effect of Wealth on Cigarette and Waterpipe Smoking

Abstract: Introduction: The presence of social inequalities in tobacco-use has been fully recognized in the international literature. Even though cigarette and waterpipe tobacco smoking (WTS) are prevalent in the Arab region, the literature has not addressed the social determinants of the impending tobacco epidemic. This study examined the socioeconomic patterning of cigarette and WTS among Jordanian women. Methods: We analyzed pooled data from four waves of the Jordan Demographic and Health Surveys: 2002 (N = 5851); 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
1
14
4
Order By: Relevance
“…The present results revealed that HS among the ever-married group was many times as frequent as the never-married. With this respect, some research found a higher rate of HS among widows and divorcees than the single individuals [55]. Some other research, however, reported that perceived family norms of the married people can in uence their intention to ease smoking [56].…”
Section: Discussionmentioning
confidence: 99%
“…The present results revealed that HS among the ever-married group was many times as frequent as the never-married. With this respect, some research found a higher rate of HS among widows and divorcees than the single individuals [55]. Some other research, however, reported that perceived family norms of the married people can in uence their intention to ease smoking [56].…”
Section: Discussionmentioning
confidence: 99%
“…However, published reports suggest no difference in tobacco smoking prevalence between Palestine refugees living inside or outside refugee camps [ 15 ]. Outside the refugee setting, it appears both cigarette and waterpipe tobacco smoking are associated with increased wealth among women in Jordan [ 23 ]. Interestingly, it appears that the association between waterpipe tobacco smoking and high socioeconomic status remains even in societies where cigarette smoking is associated with low socioeconomic status [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a region where public health systems are under-funded and ill-equipped to address the disproportionate burden of smoking-related NCDs, robust evidence on social inequalities in this important behavioral risk factor among Arab populations is scarce. Only a handful of studies have examined associations between SES and cigarette smoking, revealing that the behavior is inversely associated with both education among adults [ 21 , 22 ] and parental education among adolescents [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%